2011
DOI: 10.1161/circgenetics.110.958371
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) Genetic Variants Associated With Coronary and Peripheral Vascular Disease but Not With Stroke Risk in the Heart Protection Study

Abstract: Background— Genetic studies have identified 2 single-nucleotide polymorphisms (SNPs) at the LPA locus (rs3798220 and rs10455872) that are strongly and independently related to lipoprotein(a) levels and to coronary disease risk, but their relevance for other atherothrombotic disease is uncertain. Methods and Results— These 2 LPA SNPs were examined together … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 25 publications
1
37
0
Order By: Relevance
“…At least 1 risk allele was detected in 61.3%, in comparison with only 9.0% and 20.6% in PROCARDIS and the Heart Protection Study. 6,14 There was no difference in event rates between risk allele carriers and those without risk alleles. The difference between Lp(a) concentrations of patients with and without risk alleles was not clinically relevant.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…At least 1 risk allele was detected in 61.3%, in comparison with only 9.0% and 20.6% in PROCARDIS and the Heart Protection Study. 6,14 There was no difference in event rates between risk allele carriers and those without risk alleles. The difference between Lp(a) concentrations of patients with and without risk alleles was not clinically relevant.…”
Section: Discussionmentioning
confidence: 86%
“…Information from the 2 single-nucleotide polymorphisms was combined into a single LPA genotype. 6,14 Outcome Parameter…”
Section: Laboratory Measurementsmentioning
confidence: 99%
“…33 In prospective studies, rs3798220 was associated (1) with incident MI among 3849 Caucasian men and women age 65 years or older in the Cardiovascular Health Study (CHS), 36 (2) with incident major cardiovascular events (including MI, ischemic stroke, and cardiovascular death) among 25 131 initially healthy women age 45 years or older in the Women's Health Study (WHS), 29 and (3) with incident CHD (a composite of MI, CHD death, and coronary revascularization) among 5330 aspirin nonusers (but not among 1422 aspirin users) age 45 to 64 years in the Atherosclerosis Risk in Communities (ARIC) study. 38 This SNP was not associated with incident CHD among 14 465 participants in the HPS study 39 or with incident CHD among 1328 men and 1552 women in the Framingham Offspring study. 40 In a meta-analysis that combined results from these case-control and prospective studies (see Methods and online-only Data Supplement Materials), carriers of the 4399Met allele had a 57% increased risk of CHD, compared with noncarriers (Pϭ1.04ϫ10 Ϫ11 , Figure 2A).…”
Section: Association Of Lpa Variants With Cardiovascular Diseasementioning
confidence: 95%
“…The intronic rs10455872 SNP was reported to be associated with CHD 30 and with MI 35 in case-control studies and with incident CHD in a prospective study. 39 In a meta-analysis of these studies (see Methods and online-only Data Supplement Materials) the risk of CHD was 42% higher per copy of the minor allele (G) of rs10455872 (11% of the Caucasian populations carry at least 1 G allele; Table) (Pϭ3.80ϫ10 Ϫ6 , Figure 3). The rs10455872 and rs3798220 SNPs are 49 kb apart and are not in linkage disequilibrium (r 2 Ͻ0.01).…”
Section: Association Of Lpa Variants With Cardiovascular Diseasementioning
confidence: 99%
“…18 In contrast, a genetic study reported that an LPA genotype score that explains about a third of the variation in Lp(a) levels, and was strongly associated with CHD, was not associated with prevalent or incident IS in those with or without previous CHD. 19 In a subsequent study, Helgadottir et al 20 reported that LPA alleles associated with higher Lp(a) levels were associated with higher risk of large artery IS, but not with either cardioembolic or small vessel IS. Thus, any impact of Lp(a) levels on IS may be subtype specific.…”
Section: Lipoprotein(a)mentioning
confidence: 97%